Smart handicapped parking system using fingerprint / Herwan Mohd Jemi - Mohd Jemi, Herwan (Faculty of Computer and Mathematical Sciences, 2016)
The main purpose of this study which is to proposed a systematic handicapped parking management where it focus to tackle the issue of exploitation on handicapped parking facilities. The aim of project development which is to solve the problems that faced by disabled person in handicapped parking bay. Therefore this project propose the Smart Handicapped Parking System using the fingerprint method for prevention of duplication and also misuse of handicapped parking bay. Thus, current method in managing the parking is not efficient as it is denying the real user right. Smart Handicapped Parking System is developed to automatically authenticate registered user and unlock the barrier at handicapped parking bay. By using Arduino board and fingerprint reader, the system read fingerprint of the person, and compare with registered user in database. The fingerprint has been choose to be the most suitable method due to the uniqueness of fingertip itself, where this features cannot be duplicate and misuse by anyone. The Arduino microcontroller is used for developing the prototype version due to the size and also the capabilities to supply most important hardware component that related to this project such as, Micro servo, Ultrasonic sensor, Fingerprint reader, and also the Arduino board. This project capable to be a stand-alone project without need to be connected through computer after the configuration process. Besides that, this smart parking system has been tested with real disabled person and leaving with the positive feedback as expected. However, this smart parking system is excellent to be used not only for handicapped parking, but also to other closed parking system, such as residential parking, monthly paid parking space and etc. In the future, this project will be able to be widely implement in larger area by having the online database for online synchronization.